Testing a Nonlinear Solution of the Israel–Stewart Theory - Cruz-Marin, N (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this work, we test the ability of an exact solution, found in the framework of a nonlinear extension of the Israel–Stewart theory, to fit the supernovae Ia, gravitational lensing, and black hole shadow data. This exact solution is a generalization of one previously found for a dissipative unified dark matter model in the context of the near-equilibrium description of dissipative processes, where we do not have the full regime of the nonlinear picture. This generalized solution is restricted to the case where a positive entropy production is guaranteed and is tested under the condition that ensures its causality, local existence, and uniqueness. From the observational constraints, we found that this generalized solution is a good candidate in the description of the observational late-time data used in this work, with best-fit values of (Formula presented.), (Formula presented.), (Formula presented.), (Formula presented.), and (Formula presented.), at a (Formula presented.) of confidence level. We show that the nonlinear regime of the Israel–Stewart theory consistently describes the recent accelerated expansion of the universe without the inclusion of some kind of dark energy component and also provides a more realistic description of the fluids that make up the late universe. © 2024 by the authors.